Antioxidant, α-glucosidase inhibitory activities, and HPLC quantitative analysis of phenolic compounds isolated from Neptunia oleracea Lour. - Lee, Soo Yee; Ismail, Intan Safinar; Ang, Eng Loo; Abas, Faridah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
Neptunia oleracea Lour. is a tropical plant cultivated in Southeast Asia. It is consumed as vegetable and traditional herb for the treatment of several disorders. The objective of the present work was to isolate the phenolic compounds from N. oleracea, followed by their bioactivity evaluation and quantitative analysis. The ethyl acetate (EtOAc) and methanol (MeOH) fractions of N. oleracea were subjected to various chromatographic techniques to isolate the phenolic compounds. The isolated phenolic compounds were characterised by several spectroscopic methods, including mass spectrometry (MS) and nuclear magnetic resonance (NMR). Then, these compounds were subjected to DPPH free radical scavenging as α-glucosidase inhibitory assays for the evaluation of their activities. Their contents in the fractions were analysed via high performance liquid chromatography (HPLC) quantitative analysis. Five phenolic compounds including quercetin-3-O-β-D-xylopyranoside (1), quercetin-3-O-α-L-arabinopyranoside (2), quercetin-3-O-α-L-rhamnoside (3), methylgallate (4) and rutin (5) were isolated from N. oleracea for the first time. Evaluation on the DPPH free radical scavenging and α-glucosidase inhibitory activities of these compounds showed that methylgallate (4) was the most potent antioxidant and α-glucosidase inhibitors among them, with IC50 values of 17.25 and 50.76 μM, respectively. The HPLC quantitative analysis revealed the high content of the quercetin derivatives (compounds 1, 2 and 3) in the EtOAc fraction (ranging from 125.68 to 157.55 μg/mg) and methylgallate (4) in the MeOH fraction (75.25 μg/mg). Comparison of the bioactivities of the isolated phenolic compounds with the fractions indicated their significant contribution for the DPPH free radical scavenging of N. oleracea; while they might be working synergistically for the α-glucosidase inhibitory activity. The results of the present work could help to validate the contribution of phenolic compounds for the studied bioactivities of N. oleracea.